Cosmology, Lensing, and Modified Gravity with Gravitational Waves - (:unkn) unknown (My University, 2023)
Since the first detection of gravitational waves (GWs) from the merger of two stellar-mass black holes in 2015, the LIGO-Virgo-KAGRA (LVK) Collaboration has accumulated over 90 observations of mergers involving neutron stars and black holes. With the upcoming observing runs for the LVK network of GW detectors, many more binary mergers are expected to be detected. The increasing size of gravitational wave catalogs has enabled the study of their population, its cosmic expansion history, signatures of gravitational wave lensing, and how well these observations agree with general relativity. In this dissertation, I will discuss my contributions to gravitational wave cosmology. I will focus on the development of the dark siren methodology and how it was used with the GWTC-1 catalog to provide a first joint measurement of the Hubble constant from GW standard sirens. I will also discuss a joint parameter estimation framework developed to identify and characterize pairs of strongly lensed GWs from binary black hole mergers and how it was was applied to GWTC-1 observations. Finally, I will explore two topics related to testing modifications to general relativity. First, I will describe how we used the strong lensing joint parameter estimation framework to measure the presence of alternative polarization modes in GW signals from BBH mergers, including a fully mixed tensor, vector, and scalar mode model. Second, I will discuss my work on modified GW propagation in the context of gravitational leakage models, which predict the existence of large extra spacetime dimensions. Using the latest GWTC-3 catalog, we provided the first constraints on such extra-dimension models using BBH mergers.
Keywords: black holes; cosmology; general relativity; gravitational lensing; gravitational waves; neutron stars